A hybrid topological and structural optimization method to design a 3-DOF planar motion compliant mechanism - Lum, Guo Zhan (2013)
This paper proposes a novel design methodology to synthesize flexure-based parallel manipulators (FPM) for high precision micro/nano-scale manipulation. Unlike traditional synthesis methods, the proposed method uses a structural optimization algorithm that is independent of human intuition, to synthesize compliant joints with optimal stiffness characteristics. This algorithm is able to evolve the topology and shape of the compliant joints. Based on finite element analysis, the synthesized compliant joints are able to achieve better stiffness characteristics than the traditional compliant joints. This allows the synthesized joints to achieve a large deflection range while maintaining their capabilities to resist external wrenches in the non-actuating directions. A planar motion FPM with a workspace of 4 mm2 × 2° is formed by assembling the optimal compliant joints. The actuating compliance of the joints and FPM are validated by experiments and their deviation between the experimental results and the simulation prediction are within 10% and 18% respectively.